Price and wage setting in an integrating Europe: firm level evidence - Filip Abraham; Jozef Konings; Stijn Vanormelingen (National Bank of Belgium, 2006)
Europe has witnessed the last decade an accelerated process of economic integration. Trade barriers were removed, the euro was introduced and ten new member states entered the European Union. Economic integration is likely to have an impact on both labor and product markets. Unlike most other papers, that focus on product and labor markets separately, we look at the link between globalization and product and labor market imperfections simultaneously. To this end, we rely on a rich panel of manufacturing firms in Belgium, a small open economy. We find that union bargaining power is higher in sectors characterized by high price cost margins. Moreover, ignoring imperfections on the labor market, leads to an underestimation of product market power. Concerning the influence of globalization, our main findings are that both price cost margins and union bargaining power are typically lower in sectors that are subject higher international competition. This result is especially true for competition from low wage countries
Keywords: F16; J50; L13; 330; Mark-ups; Trade Unions; International Trade; Gewerkschaftsmitgliedschaft; Verhandlungstheorie des Lohnes; Schätzung; Industrie; Belgien